PENGARUH JAM KERJA DAN TARIF TERHADAP PENDAPATAN DRIVER GOJEK (GO-RIDE) DI KECAMATAN GUBENG KOTA SURABAYA - Nur Fakhri Febriansyah; Joko Priyono (Nirta Learning Centre, 2025)
This study aims to analyze the effect of working hours and fare rates on the income of Gojek (Go-Ride) drivers in Gubeng District, Surabaya City. The research is motivated by the significant growth in the number of online motorcycle taxi drivers and the income instability they face, which is presumed to be influenced by factors such as working hours and fare kilometers. A quantitative method was employed using survey techniques through questionnaires distributed to 100 selected Gojek drivers using purposive sampling. Analysis data were analyzed using multiple linear regression analysis. The results indicate that both working hours and fare rates have a positive and significant effect on driver income, both simultaneously and partially. The study concludes that an increase in working hours and proper fare adjustments directly impact the income growth of Gojek drivers in the area. These findings are expected to serve as useful input for ride-hailing companies and policymakers in formulating fair and productive regulations for driver-partners.